Analysis of Teamwork Dynamics and Its Impact on Sales Performance at PT Ramayana Lestari Sentosa Tbk Medan - Lubis, Devi Aprilia; Wijaya, Rangga Hadi; Sampurno, Muhammad Akbar; Nisa, Zahratun; Syahreza, Dina Sarah; Harmen, Hilma (Economic: Journal Economic and Business, 2024)
This research aims to find out how teamwork influences sales performance at PT Ramayana Lestari Sentosa Tbk Medan. Sales performance is the level of company effectiveness in achieving the desired results from sales activities. The subjects in this research were employees, specifically SPG PT Ramayana Lestari Sentosa Tbk Medan. The type of research that the author uses is descriptive qualitative research. Descriptive research aims to describe a population, situation or phenomenon accurately and systematically. This research uses qualitative techniques by conducting observations, interviews and documentation studies. The research results show that teamwork influences sales performance at PT Ramayana Lestari Sentosa Tbk Medan. Good teamwork can improve sales performance, while poor teamwork can reduce sales performance.